ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT MENABUNG DI BANK SYARIAH INDONESIA - Eka Fariani; Muhammad Haris Riyaldi; Yani Prihatina Eka Furda (FAKULTAS SYARIAH DAN EKONOMI ISLAM UNIVERSITAS ISKANDARMUDA BANDA ACEH, 2021)
Islamic banks play an important role as a facilitator in all economic activities in the halal industry ecosystem. The existence of the Islamic banking industry in Indonesia has experienced a significant increase and development in the past three decades. On February 1, 2021, which coincided with 19 Jumadil Akhir 1442 H, it marked the history of the merging of Bank Syariah Mandiri, BNI Syariah, and BRI Syariah into one entity, namely Bank Syariah Indonesia (BSI). This merger will unite the advantages of the three Islamic banks so as to provide complete services, a wider reach, and have a better capital capacity. Bank Syariah Indonesia is encouraged to be able to compete at the global level. This study aims to analyze the knowledge, promotions and facilities influencing the interest of the people of Banda Aceh City to save their money at Bank Syariah Indonesia. The research method used is quantitative research methods. Data was collected through questionnaires distributed to the people of Banda Aceh City. Samples were taken as many as 100 respondents with simple random sampling technique. The data obtained were then processed using the IBM SPSS version 28 program. This analysis included validity tests, reliability tests, classical assumption tests, multiple regression tests and hypothesis testing. The results of the simultaneous test show that knowledge, promotion and facilities together affect the public's interest in saving at Bank Syariah Indonesia.